Pengujian Black Box Testing Pada Sistem Website Osha Snack: Pendekatan Teknik Boundary Value Analysis - Kartono, Fatih Kawakib; Nursaadah, Syifa; Nugroho, Mario Raditya; Tama, Dimas Akbar; Mashudi, Ferrol Azki; Wicaksono, Aditya; Nasir, Muhammad (Jurnal Kridatama Sains dan Teknologi, 2024)
This study functional quality testing of the Osha Snack website was conducted using the Black Box Testing method with the Boundary Value Analysis (BVA) technique approach. Osha Snack is an e-commerce platform that provides online-based snack products. Black Box Testing was chosen because of its ability to rotate the system without checking the internal code, focusing on the input and output provided by the user. BVA tests input limits, such as minimum, maximum, and out-of-bounds values, to identify potential problems in the most vulnerable areas. The test results show that the system successfully handles valid input according to functional specifications and provides effective validation for input that exceeds the desired limits, with a percentage reaching 96% of all tested scenarios. This technique has been shown to improve the accuracy and stability of the system with wide test coverage but is efficient in terms of time and resources. However, BVA has limitations, namely it does not cover internal logic testing and does not detect errors outside the tested boundaries. This study significantly contributes to developing a more reliable e-commerce platform through an optimal software testing process.